Psychopathy caused of the main character in Flynn’s Gone Girl - Syahidah, Muthi; Nasmilah, Nasmilah; Pammu, Abidin (Universitas Wiralodra, 2023)
In this research, the researcher aimed to investigate the psychopathy cause of the main character in Flynn’s Gone Girl. This research used a descriptive qualitative method. The data were collected through closed reading. This research showed that the main character's journey is unquestionably satisfying from start to finish. The effects of the main character's actions have reached a point of saturation, and they are extremely happy. Several minor characters have thwarted the main character's magnificent plot to exact revenge on the other main character (her husband). This research suggests further research to analyze the social relationship between the characters of the novel and its impact on their character. Specifically, the researcher analyzed the main character who is a psychopath and it has fascinated artists and the general public for centuries. Besides, it also got the author’s feelings or experiences of the object of the study in Flynn’s Gone Girl.